Microfungi associated with dead caterpillars and spiders in Xishuangbanna Tropical Botanical Garden, P.R. China - Yang, Er-Fu; Karunarathna, Samantha C.; Priyashantha, Alviti Kankanamalage Hasith; Promputtha, Itthayakorn; Chen, Xuemei; Elgorban, Abdallah M.; Bashir, Nawaz Haider; Tibpromma, Saowaluck; Dossa, Gbadamassi G. O. (Phytotaxa, 2024)
During an investigation of microfungi associated with insects in the tropical region of Yunnan Province, China, dead fungi infected within several caterpillars and spiders in the Xishuangbanna Tropical Botanical Garden were found. Two selected fungal strains were isolated from the surface of the cadavers and subjected to morphological and molecular identification. Phylogenetic analyses were carried out on the subsequent isolates based on multiple gene sequences (ITS, LSU, SSU, rpb1, gapdh, and tef1-α). The observations and the analyses confirmed that the fungi belong to Curvularia geniculata (associated with dead caterpillars) and Purpureocillium atypicola (associated with dead spiders). Here, we have given detailed descriptions of the species along with photo plates and phylogenetic trees showing their taxonomic placements.